A reduced-basis element method for pin-by-pin reactor core calculations in diffusion and SP3 approximations. (June 2018) - Cherezov, Alexey; Sanchez, Richard; Joo, Han Gyu
Highlights: The Reduced Basis Element Method (RBEM) is suggested as an alternative to computationally intensive large high-fidelity calculations. The RBEM is based on the calculation of ad-hoc reduced basis functions and the application of the Discontinuous Galerkin method. The RBEM is applied to multigroup diffusion and SP 3 reactor core pin-by-pin calculations. Abstract: The reduced order model (ROM) methods allow to significantly improve the computation time and memory usage. Therefore these methods are very useful for real-time or many-query reactor core simulation analysis. The ROM approach is based on the proper orthogonal decomposition methods which generate an optimal truncated subspace from a given set of test solutions or snapshots. In the case of high-fidelity real-size problems the calculation of one snapshot might be too expensive or not possible due to memory limitations. To circumvent this problem we apply the reduced basis element method (RBEM). This method is based on a spatial decomposition of the core domain and on the application of the ROM approach on each subdomain. In this work the RBEM is developed for diffusion and SP 3 equations and the results are illustrated with several two-dimensional reactor core calculations.